Vulnerabilidade em saúde de gestantes hospitalizadas com Covid-19: estudo de casos múltiplos - Castro, Antonia Tainá Bezerra (2023)
The COVID-19 pandemic caused by SARS-CoV-2, emerged at the end of 2019 in Wuhan, Hubei province, China, which spread across all continents, exponentially increasing the number of infected and causing thousands of deaths in the world. Thus, conditions for possible flu complications were listed, as is the case for pregnant women at any stage of pregnancy. The objective was to analyze the elements of vulnerability in the health of pregnant women hospitalized with COVID-19. The method used was a multiple case study carried out with seven women, residents in the municipality of Sobral/CE, who were infected with COVI-19 during pregnancy and remained hospitalized at Santa Casa de Misericódia de Sobral from March 2020 to March de 2022. Data collection took place between May and June 2023. For data analysis, the Content Analysis Technique proposed by Bardin and the Crossed Synthesis of Cases based on the theoretical framework of Health Vulnerability were applied. Iramuteq software is also used to present the data. From the immersion and analysis of the interviews, 30 registration units were identified and classified into 4 categories grouped according to the elements of vulnerability in health. Related to the subject: Psycho-emotional situation of women facing COVID-19 and Interpersonal relationships of women diagnosed with COVID-19. Regarding the social element: Women's support networks during pregnancy and the puerperium and Programmatic situation of health services that care for women who had covid-19 during pregnancy. The research was approved by the Research Ethics Committee under opinion number 5,958,313. Thus, the study of multiple cases allowed the recognition of dichotomies and conformity between the health vulnerabilities experienced by women in their different contexts. Different situations of health vulnerability experienced by them were found, which give rise to emotional imbalances, precariousness in interpersonal relationships and weaknesses in management and in the work process.